Guest editorial special section on cyber-physical systems in green transportation - Hu, X. (2020)
The papers in this special section focus on cyber-physical systems in green transportation. Ground mobility is being in a paradigm shift toward more efficient and green transportation. Wireless networking, sensing, computing, and control advances have significantly changed the way the society interacts with the physical world. In the context of cyber-physical systems (CPS), transportation systems become highly multidisciplinary. They require an ever-increasing integration of mechanical, electrical/ electronic, control, and information disciplines. Emerging innovative technologies, such as automated driving and electrified vehicles, are also profoundly promoting connection, automation, and electrification of the current transportation sector.